Information support of the geological sector of Russian Federation - L. E. Chesalov; O. V. Mitrakova (Известия высших учебных заведений: Геология и разведка, 2017)
The current state of the information support of the geological sector and the different factors, complicating its development have been analyzed. Organizational, technical and other aspects have been considered. The principles of the development of the information support have been proposed and the organizational and methodic measurements of its improvement have been marked out, such as one-shot and safe input of the information; personified responsibility for the operational efficiency and accuracy; accessibility and gratuitousness of the information transmission, except the information with access, limited by the low; the design and maintenance of the base list-registers (basic systems).